“A grande obra educadora”: a Associação de Escoteiros do Alecrim / Natal-RN (1919-1967) - Leandro, Andressa Barbosa de Farias (2020)
This thesis objective to analyze the historical path of the Scout Association of Alecrim (A.E.A), located in the city of Natal, between the years 1919 to 1967. The chosen time frame took into account the fact that the history of A.E.A is intrinsically linked to that of its founder, the teacher Luiz Soares, so the delimitation privileged as an initial milestone, the year of the foundation of A.E.A and as a final mark, the year of the death of its founder. Ahead of his leadership for forty-eight years, this educational intellectual introduced new educational practices in that space initially thought for the practice of scouting, such as professional and musical education and an educational cinema, thus imparting unique characteristics to the EA, which set it apart from other Scout associations in the country. Recognized of public utility by Law No. 491, of December 1, 1920, due to its high educational purpose, the AEA has consolidated itself as an educational institution that had a relevant role for the education of children and young people from Natal, as well as for the society of generally speaking. The research pointed out that, despite innovating with regard to the introduction of new educational practices, the A.E.A did not lose sight of the principles of Scouting, such as civic and moral values, obedience and discipline, however despite the disciplinary mechanisms that permeated this educational space, we identified some deviationist practices, such as participation in games of chance, absences in Scout activities, suspensions and even expulsions, indications that not all Scouts were as devoted to passivity and discipline as teacher Luiz Soares expected. As for the theoretical-referential, we spoke with Magalhães (2004), who provided us with subsidies to analyze A.E.A as an educational institution inserted in the context and historical circumstances of the city of Natal; with Sirinelli (2003), whose considerations about the concept of intellectual were extremely important to think about the figure of professor Luiz Soares and his networks of sociability; Foucault (1987), who helped us with his discussions on disciplinary power and Certeau (1994), who provided subsidies to understand the strategies and tactics of the subjects who went through the A.E.A. The documentary corpus consisted of Laws, Decrees, Government Messages, Regulations and Statutes, letters, correspondence, newspapers, magazines and photographs. Theoretical-methodological choices made it possible to think of A.E.A beyond scouting practices, that is, as an educational institution, centered on the figure of its founder, in which diverse ideas, knowledge and interests circulated.